2014
DOI: 10.1186/s13054-014-0527-8
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced monocyte chemoattractant protein-1 production in aging mice exaggerates cardiac depression during endotoxemia

Abstract: IntroductionEndotoxemia and the systemic inflammatory response syndrome have a significant impact on post-surgery outcome, particularly in the elderly. The cytokine response to endotoxin is altered by aging. We tested the hypothesis that vulnerability to endotoxemic cardiac depression increases with aging due to age-related augmentation of myocardial inflammatory responses.MethodsAdult (4 to 6 months) and old (20 to 22 months) C57/BL6 mice were treated with endotoxin (0.5 mg/kg, iv). Left ventricle (LV) functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 42 publications
3
30
0
Order By: Relevance
“…As enhanced MCP-1 production and mononuclear cell accumulation in the myocardium play important roles in the exaggerated cardiac dysfunction in old endotoxemic mice [4], we compared MCP-1 levels and myocardial mononuclear cell density in old WT mice and old IL-37tg mice. As shown in Figure 3A, MCP-1 levels in plasma and myocardial tissue after LPS treatment were significantly lower in old IL-37tg mice in comparison to old WT mice (420±32 pg/ml vs. 1318 pg/ml±128 pg/ml and 310±23 pg/mg vs. 692±56 pg/mg, both P <0.05).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As enhanced MCP-1 production and mononuclear cell accumulation in the myocardium play important roles in the exaggerated cardiac dysfunction in old endotoxemic mice [4], we compared MCP-1 levels and myocardial mononuclear cell density in old WT mice and old IL-37tg mice. As shown in Figure 3A, MCP-1 levels in plasma and myocardial tissue after LPS treatment were significantly lower in old IL-37tg mice in comparison to old WT mice (420±32 pg/ml vs. 1318 pg/ml±128 pg/ml and 310±23 pg/mg vs. 692±56 pg/mg, both P <0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Excessive production of pro-inflammatory mediators caused by bacterial lipopolysaccharide (LPS) frequently leads to cardiac dysfunction. We and others have observed that LPS induces cardiac contractile depression through up-regulation of myocardial production of pro-inflammatory cytokines, such as tumor necrosis factor-α (TNF-α), interleukin (IL)-1β, and IL-6 [24]. Importantly, morbidity and mortality due to the systemic inflammatory response syndrome associated with trauma or sepsis are significantly increased in the elderly [5, 6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the inflammatory molecules that plays a role in the human ovulatory process and relates to both aging and obesity [14][15][16][17][18][19] is monocyte chemoattractant protein-1 (MCP-1) [20]. MCP-1, a polypeptide composed of 76 amino acids, is produced by various cell types including endothelial cells, fibroblasts, tumor cells, monocytes, and macrophages [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…In humans, physiologic levels of MCP-1 are important for the ovulatory process [20]. As far as aging and obesity, data have shown that systemic MCP-1 levels are increased in aging animals [14][15][16] and that there is an increased abundance of this pro-inflammatory chemokine in both white adipose tissue and plasma in obese animals [17][18][19]. Additionally, we have recently demonstrated in women undergoing in vitro fertilization (IVF) that serum and follicular fluid MCP-1 are positively correlated with body mass index (BMI) (Obehi et al, manuscript under review).…”
Section: Introductionmentioning
confidence: 99%